Follow-up of transcatheter closure of congenital heart disease complicated with pulmonary arterial hypertension in children - Huang, Yanyun; Chen, Yuting; Su, Danyan; Qin, Suyuan; Chen, Cheng; Liu, Dongli; Ye, Bingbing; Huang, Yuqin; Yuan, Piaoliu; Pang, Yusheng (Frontiers in Pediatrics, 2025)
BackgroundTranscatheter closure is now the preferred treatment for congenital heart disease complicated with pulmonary arterial hypertension (CHD-PAH), but its long-term effects are not well understood. We aimed to assess the safety, effectiveness, and outcome of this procedure in children with CHD-PAH.MethodsWe included 210 children with CHD-PAH at our hospital from 2012 to 2021 and collected their general, laboratory, echocardiographic, and hemodynamic data for analysis. A logistic regression analysis identified risk factors for persistent postclosure PAH (PP-PAH).ResultsAmong the 210 patients, 84.29% had mild PAH, 8.57% had moderate PAH, and 7.14% had severe PAH. The device was successfully implanted in 98.10% of patients. Early adverse events occurred in 12.14% (n = 25) of patients, with residual shunts and arrhythmia being the most common complications, each affecting 2.91% (n = 6) of patients. Most complications were minor and temporary, except for two cases of residual shunt—one required surgical repair, and one case of complete left bundle branch block led to occluder removal. Postintervention, pulmonary arterial pressure (PAP) decreased significantly, and cardiomegaly resolved. PP-PAH was detected in 13 patients (6.31%). Preoperative pulmonary arterial systolic pressure [odds ratio [OR] = 1.033, 95% confidence interval [CI] = 1.005–1.061, P = 0.019] and right ventricular diameter (OR = 1.111, 95% CI = 1.039–1.187, P = 0.002) were found to be risk factors for PP-PAH.ConclusionTranscatheter closure is effective and safe for children with correctable CHD-PAH. Preoperative pulmonary arterial systolic pressure and right ventricular diameter are risk factors for PP-PAH.